2004
DOI: 10.1126/science.1104276
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Carbon Nanotube Yarns by Downsizing an Ancient Technology

Abstract: By introducing twist during spinning of multiwalled carbon nanotubes from nanotube forests to make multi-ply, torque-stabilized yarns, we achieve yarn strengths greater than 460 megapascals. These yarns deform hysteretically over large strain ranges, reversibly providing up to 48% energy damping, and are nearly as tough as fibers used for bulletproof vests. Unlike ordinary fibers and yarns, these nanotube yarns are not degraded in strength by overhand knotting. They also retain their strength and flexibility a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
1,218
6
13

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,626 publications
(1,282 citation statements)
references
References 16 publications
26
1,218
6
13
Order By: Relevance
“…[36,38] The strength of as-spun GO fiber is also much higher than single yarns of pure multi-walled CNTs (~250 MPa). [40] It should be noted that the GO used in this study is much larger compared to "giant GO" [17] (37µm in this study vs 18µm), which is the basis of the enhanced improvement in mechanical properties attained in the current study.…”
Section: Mechanical Propertiesmentioning
confidence: 97%
“…[36,38] The strength of as-spun GO fiber is also much higher than single yarns of pure multi-walled CNTs (~250 MPa). [40] It should be noted that the GO used in this study is much larger compared to "giant GO" [17] (37µm in this study vs 18µm), which is the basis of the enhanced improvement in mechanical properties attained in the current study.…”
Section: Mechanical Propertiesmentioning
confidence: 97%
“…This interface is schematically illustrated as a tapered zone in Figure 3a 6 and a 8 , where Schottky barrier modulation of SWNT-FETs takes place. [104] Normally, adsorption of the biomolecular recognition moieties occurs not only onto nanotube sidewalls but also on this tapered-thin metal-SWNT Schottky junction.…”
Section: Transistor Based Biosensorsmentioning
confidence: 99%
“…[1][2][3] CNTs have the potential to revolutionize numerous applications where nano-sized metallic and/or semiconducting components are required along with high strength, [4,5] large flexibility [6] and superb chemical stability. [7,8] In particular, metallic (met-) nanotubes are highly suited for nanoscale circuits, [9] ultrathin, flexible, and transparent conductors, [10] supercapacitors, [11] field emitters, [12] actuators, [13] and nanosized electrochemical probes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, prior to 2007, the reported tensile strengths of continuous CNT fibers without a coagulant lay in the range from 0.4 to 1.2 GPa, no matter if they were spun from a suspension. [5][6][7][8][9][10][11][12] Recently, Windle et al reported the synthesis of continuous high-performance CNT fibers with the highest strength value of 9 GPa. [12] This encouraging breakthrough enlightens the use of macroscale CNTs fibers as a structural reinforcement for many applications.…”
mentioning
confidence: 99%
“…Figure 1 shows a typical twisting process. Compared with the existing spinning methods developed by other groups, [5][6][7][8][9][10][11] our twisting method may not be suitable for continuous production of CNT fibers, but the control of the diameters and twisting degrees is more convenient. So the fabricated fibers are ideal systems for the study of CNT macroarchitectures.…”
mentioning
confidence: 99%